Efficacy of rifaximin among non-constipated irritable bowel syndrome patients with or without small intestinal bacterial overgrowth: a randomized, double-blind, placebo-controlled trial - Podder, Subrata; Masudur Rahman, M.; Hossain, Mohammad Iqbal; Datta, Raj; Alam, Jane; Golam Kibria, M. (International Journal of Research in Medical Sciences, 2024)
Background: IBS is a functional gastrointestinal disorder marked by abdominal pain and changes in stool frequency or form. Recent studies indicate a link between IBS, especially the diarrhea-predominant subtype, and small intestinal bacterial overgrowth. This study aimed to evaluate symptom resolution among IBS patients with or without SIBO on rifaximin treatment as compared with placebo. Methods: A double-blind, placebo-controlled, randomized clinical trial took place at the Department of Gastroenterology, Dhaka Medical College and Hospital, from January to December 2019. In the study 104 non-constipated IBS patients were assessed for SIBO using gut aspirate culture. Those with SIBO (≥105 CFU/ml) and those without were randomly assigned (computer-generated) to receive either 1500 mg/day of rifaximin for 14 days or a placebo. Results: Among 104 non-constipated IBS patients, 39% had SIBO, with IBS-D patients more associated (83% vs. 60%). Rifaximin significantly improved symptoms in the SIBO group at 4 and 16 weeks (90% vs. 20%, p<0.001; 66% vs. 15%, p<0.001). In the non-SIBO group, significant improvement was observed at 4 weeks (38.7% vs. 18.8%, p<0.001) but not at 16 weeks (25.8% vs. 18.8%, p=0.501). Rifaximin significantly improved abdominal pain, stool form, and frequency in the SIBO group compared to placebo. However, there was no significant improvement in the non-SIBO group. Conclusions: Rifaximin is superior to placebo in relieving symptoms of non-constipated IBS patients with SIBO.